World picture of opinion leaders 1974 - Hedman, Lowe (Uppsala University, 1984)
The research project 'Information strategies - analysis and evaluation of trials to spread information on developing countries through multimedia' was requested to evaluate an information campaign on developing countries generally, and Tanzania especially. The campaign was namned Karibu-project and data was gathered in several surveys. The aim of this survey was to illustrate some issues regarding the conception of 'world picture'. The survey includes information on the respondent´s interest in different subject fields in mass media, opinion on the future prospects for different groups in society, and threats against the future. Furthermore the respondent was asked about the reason of why some countries are poor, her/his attitude to different kinds of help to developing countries, and reason for being concerned with/not concerned with developing countries. Other questions dealt with the respondent´s knowledge about developing countries and judgement of the policy held by different political parties. Most of these questions can be found in Information about developing countries (SSD 0146), and a smaller number in Daily press journalists and the foreign information (SSD 0170).

Purpose:

Illustrate some issues regarding the conception of 'world picture'

Undersökningen ingår i forskningsprojektet 'Informationsstrategier - Analys och utvärdering av försök med spridning av u-landsinformation genom multimedia'. Syftet med denna undersökning var att belysa en del frågeställningar kring begreppet 'världsbild'; hur man ser på samhällets utveckling och utvecklingsmöjligheter; hur man strukturerar händelser och händelseförlopp; om man har en personligt inriktad problemorientering eller om man ser problemen i ett nationellt eller internationellt perspektiv.
I undersökningen ställdes frågor om respondentens intresse för olika innehåll i nyheter och artiklar i tidningar, radio och tv; uppfattning om framtidsutsikten för människor i olika samhällsgrupper; faktorer som kan medföra ett hot mot framtiden; egna aktiviteter; orsaker till att vissa länder är fattiga; olika hjälpformers värde; sannolikheten att man själv argumenterar för en sak man tror på; bedömning av de politiska partiernas politik; kunskap om u-länder; attityder till frågor om u-landsproblem och levnadsstandard; massmedieanvändning; hjälp till fattiga länder; lämpliga mottagare av svensk u-hjälp; anledning till engagemang i u-landsfrågor; anledning till icke-engagemang i u-landsfrågor; förändringar i världen under de senaste årtiondena; regelbunden tidningsläsning; aktiva opinionsgrupper på orten.

Syfte:

Belysa en del frågeställningar kring begreppet 'världsbild'
Opinionsledares världsbild 1974
Keywords: Media; Media; Information society; Informationssamhället; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap